The Effectiveness of School Principals' Leadership Style in Improving Teacher Quality - Simarmata, Putri Sonia br; Pakpahan, Aida Fitri Harun; Hasibuan, Rahman Pratama; Siregar, Ahmad Rifai; Rahman, Arif; Setiawan, Deny (Jurnal Pendidikan Edutama, 2024)
This research is based on the importance of the leadership role of school principals in creating a healthy situation to improve teacher quality. This research aims to explore the effectiveness of the principal's leadership model to enhance the quality of teachers in the school, with a focus on identifying the most effective leadership style and analyzing its impact on professional development, motivation and teacher performance. The approach used in this research is a qualitative approach using the case study method. The data in this research was collected through interviews, participant observation, and thematic analysis. The research results obtained are that the principal's transformational leadership style has a significant positive impact on teacher quality, with participative leadership, open communication, and support for teacher professional development as critical factors that contribute to improving teacher quality at MAN 2 Medan.